PEMANFAATAN KEMBALI LIMBAH BATANG PISANG MENJADI KOMPOS - Sophia Shanti Meilani; Noveria Eka Susyani (Universitas Darussalam Gontor, 2021)
Organic waste frequently becomes problem in every city in Indonesia because the quantity keeps increasing while disposal area is very limited.. Most of organic waste is transported to final disposal area despite its potential to be converted into compost. This is also the case in Bekasi City. Banana stem waste is organic waste from agricultural sector, which creates problems because of its weight and volume. Composting is an alternative to treat this type of organic waste. Banana stem contains Carbon, Nitrogen, Fosfor, Kalium which are important materials for compost . This study was conducted to identify the potential of converting banana stem waste into compost. Composting of banana stem was set to 25 days. During composting process temperature increased up to 45oC. The increase of temperature indicated microorganism activity in decomposing banana stem waste. Final result of composting revealed that banana stem compost contains C-Organic, Phosphorous and moisture content that comply with the requirement of compost according to SNI 19-7030-2004. Banana stem compost also contain Kalium and Mangan but the concentration were lower than the standard. Composting of banana stem gave many benefits. It reduced organic waste quantity and the product can be reused as fertilizer. Banana waste compost provided nutrients that are required for crops productivity.